Quantitative Trait Locus Mapping and Identification of Candidate Genes Controlling Flowering Time in Brassica napus L. - Xu, Yu; Zhang, Bingbing; Ma, Ning; Liu, Xia; Qin, Mengfan; Zhang, Yan; Wang, Kai; Guo, Na; Zuo, Kaifeng; Liu, Xiang; Zhang, Miao; Huang, Zhen; et al. (Frontiers in Plant Science, 2021)
Flowering time plays a vital role in determining the life-cycle period, yield and seed quality of rapeseed (Brassica napus L.) in certain environments. Quantitative trait locus (QTL) mapping to identify the genetic architecture of genes controlling flowering time helps accelerate the early maturity breeding process. In this study, simple sequence repeats (SSR) and specific-locus amplified fragment sequencing (SLAF-seq) technologies were adopted to map the QTLs for flowering time in four environments. As a result, three target intervals, FTA09, FTA10 and FTC05 were identified. Among this, FTA09 was considered as a novel interval, FTA10 and FTC05 as stable regions. Based on the parental re-sequencing data, 7,022 single nucleotide polymorphisms (SNPs) and 2,195 insertion-deletions (InDels) between the two parents were identified in these three target regions. A total of 186 genes possessed genetic variations in these intervals, fourteen of which were related to flowering time involved in photoperiod, circadian clock, vernalization, and gibberellin pathways. Six InDel markers linked to flowering time were developed in the three target intervals, indicating the results were credible in this study. These results laid a good foundation for further genetic studies on flowering-time regulation in B. napus L.